2022
DOI: 10.1177/02676591221115260
|View full text |Cite
|
Sign up to set email alerts
|

Remote ischemic preconditioning in patients undergoing cardiac surgery with six ischemic cycles

Abstract: Background We have previously shown that remote ischemic preconditioning (RIP), which utilizes in part the extracellular RNA (eRNA)/RNase1 pathway, can induce ischemic tolerance in humans. Because RIP has thus far been tested only with four cycles of extremity ischemia/reperfusion, we investigated the influence of six cycles of ischemia on the eRNA/RNase1 pathway in cardiac patients. Methods Six cycles of RIP were carried out in 14 patients undergoing cardiac surgery. Blood samples were taken at 13 timepoints … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(21 reference statements)
0
0
0
Order By: Relevance
“…A clinical study on patients with cardiac bypass surgery found that the levels of cardioprotective RNase1 were enhanced, whereas the levels of exRNA and TNF-α were decreased upon remote ischemic preconditioning by cycles of blood pressure cuff inflation around the left arm prior to the surgery. The direct effect on cardiac function and the causality between the increase in RNAse1 and a reduction in exRNA and TNF-α were not reported in this study [128]. Consequently, the exact mechanism of RNase1-induced cardioprotection remains to be elucidated.…”
Section: Therapeutics That Alleviate Cardiac Inflammationmentioning
confidence: 63%
“…A clinical study on patients with cardiac bypass surgery found that the levels of cardioprotective RNase1 were enhanced, whereas the levels of exRNA and TNF-α were decreased upon remote ischemic preconditioning by cycles of blood pressure cuff inflation around the left arm prior to the surgery. The direct effect on cardiac function and the causality between the increase in RNAse1 and a reduction in exRNA and TNF-α were not reported in this study [128]. Consequently, the exact mechanism of RNase1-induced cardioprotection remains to be elucidated.…”
Section: Therapeutics That Alleviate Cardiac Inflammationmentioning
confidence: 63%